Digital Engagement and Guest Satisfaction: Advancing Sustainable Tourism at Boundless Bali - Ni Putu Dyah Wulandari; Dewa Made Suria Antara; Ni Gst Nym Suci Murni (Jurnal Studi Perhotelan dan Pariwisata, 2025)
Purpose: This study examines the influence of digital communication on guest satisfaction and its role in supporting perceived sustainable tourism outcomes within the specific context of slow tourism for digital nomad families at Boundless Bali.Research Methodology: A mixed-method sequential explanatory design was employed. Quantitative data were collected from 120 guests and analyzed using SEM-PLS. This was followed by a qualitative phase involving semi-structured interviews and focus group discussions with five key informants, processed through thematic analysis using NVivo 15.Results: Digital communication has a significant positive effect on guest satisfaction (T=4.880, p<0.05). The model yielded R-square values of 0.277 for satisfaction and 0.356 for sustainable tourism. Importantly, guest satisfaction serves as a significant partial mediator between digital communication and sustainable tourism (T=2.674, p=0.008).Conclusions: While digital communication facilitates operational efficiency, its impact on sustainability is primarily realized when it successfully enhances guest satisfaction. Effective digital strategies focusing on accessibility and personalization act as a mechanism for encouraging responsible travel behaviorst.Limitations: The study is limited by its reliance on self-reported data from a single site, which limits the generalizability of the findings.Contributions: This research applies the Technology Acceptance Model (TAM) and Smart Tourism Technology (STT) frameworks to the slow tourism niche, providing a model for hospitality practitioners to integrate digital tools to foster guest satisfaction and environmental awareness.